Staphylococcus aureus screening and decolonization reduces the risk of surgical site infections in patients undergoing deep brain stimulation surgery. Issue 2 (February 2017) - Lefebvre, J.; Buffet-Bataillon, S.; Henaux, P.L.; Riffaud, L.; Morandi, X.; Haegelen, C.
Summary: In a controlled before-and-after study in a single centre, it was aimed to determine whether identification of Staphylococcus aureus nasal carriers followed by nasal mupirocin ointment and chlorhexidine soap reduced surgical site infections (SSIs) among 182 patients undergoing deep brain stimulation. In all, 119 patients were included in the control group and 63 in the screening group. There was a significant SSI decrease from 10.9% to 1.6% between the two groups ( P < 0.04; relative risk: 0.13; 95% confidence interval: 0.003–0.922). There were eight SSIs involving S. aureus in the control group, none in the screening group. No specific risk factors for SSI were identified.